Z dziejów emigracji rosyjskiej w Polsce – publicystyka Michaiła Arcybaszewa - Witczak, Patryk (Acta Polono-Ruthenica, 2018)
In article was analized emigration’s journalism of Artsybashev from journal “Za svobodu!”. Journalism takes a very important place in the works of Mikhail Artsybashev. The writer witnessed historic changes in Russia of the early 20th century and emigration period and condition of Russian culture and literaturę in Russia and emigration. In his many works included a great number of valuable comments and insightful analysis of the processes taking place on the territory of the decaying Russian Empire.